Lipide-soluble vitamin contents of some Astragalus species in Turkey - Bahsi, Muammer (Mattioli 1885, 2019)
Backround: It is believed that eight astragalus speices of this study have rich vitamin contents. Purpose: To determine vitamin levels of eight Astragalus species in Turkey for the first time. Methods:1 g seed was homogenised in solvent isopropanol/hexane/ (2:3 v/v) and was treated at 10.000 g along five minutes. Afterwards, at 40 degrees C, extracts were treated on a rotary evaporator. Then, samples were prepared. All of analysis were conducted by HPLC. Seeds were dissolved in mobile phase (methanol/acetonitrile; 25/75 v/v) and were injected 50 mu L. The temperature of analytical column was performed at 40 degrees C. Detection of retinol acetate and retinol were done at 320 nm, and the detection of D2, D3, alpha-tocopherol acetate, alpha-tocopherol, delta-tocopherol were done 215 nm for, detection of K1 was done 235 nm. Authentic external standard mixtures were used to detect the vitamins. The findings obtined from analysis were represented as mu g/g. Results: beta carotene, gamma tocopherol, vitamin D3 and retinol amounts of the Astragalus species were found to be quite high. High vitamin amounts of astragalus species provide the use of these plants in the treatment of various diseases. However, alpha tocopherol and vitamin K1 values of astragalus species in the study were found to be lower than the other species belonging to other fabaceae. Conclusion: Vitamin contents of eight Astragalus species; Astragalus asterias Steven, Astragalus christianus L., Astragalus suberosus Banks & Sol., Astragalus barbatus subsp. Nanus Pon ert, Astragalus lagopoides Lam., Astragalus caniptoceras Bunge ve Astragalus cretaceus Boiss. & Kotschy were determined.
Keywords: Astragalus; lipide-soluble vitamins; HPLC